Peranan wakil rakyat dalam parti politik: Isu dan cabaran = Roles of representatives in political parties: Issue and Challenges - Brahim, Malike; Sakdan, Mohd Fo'ad; Mohamad, Musliza (School of History, Politics and Strategic Studies (PPSPS) UKM, 2013)
All elected representatives in Malaysia represent a particular political party in the legislative assembly. As community, state and national leaders, political representatives have important commitments to the political party he or she represents, and an important role in Malaysian society. However, many issues and problems can occur in political parties that affect that party’s achievements and performance during elections. Political representatives thus have a major responsibility in internal conflict resolution and, the more capable a representative, the more able he or she is in leading that party to success.This article is based on the findings of a research survey and feedback questionnaire on the theme of elected representatives.Members of Parliament and State Legislature have been selected through purposive sampling technique.One of the conclusions to be drawn from the research was that problems tend to occur in political parties because of competition for party positions, especially over the related issues of money and leadership. Political representatives were also found to have faced problems when members and elected representatives leave the party at short notice, and where there is fierce competition from the opponents’ parties during campaigning. As responsible community leaders, political representatives have a huge responsibility to their respective party to handle those challenges effectively (Stilborn: 2002).If they fail in this challenge, the impact on the party will be detrimental to the election outcome.Therefore, the ability of individual representatives to negotiate problems and come up with effective solutions are key leadership’s qualities that all political representatives must possess.